Solvability for nonlinear fractional q-difference equations with nonlocal conditions. (2018) - Wang, Jufang; Yu, Changlong; Guo, Yanping
In this paper, we study a class of nonlinear fractional q -difference equations boundary value problem. We obtain the existence and uniqueness of positive solutions for this problem by Banach's contraction mapping principle and Krasnoselskii's fixed point theorem on cone. Lastly, we give two examples to illuminate the use of the main results.